Child Labour in Iran: Problems and Solutions - Pourmohammad Golzari Nobar, Mojdeh; Arfania, Behshid; Afshari, Maryam; Taghizadeh Ansari, Mostafa (Journal of Childhood Studies)

(untitled) (Canadian Association for Young Children, 2023)
The confusion of domestic laws in integration with international laws, the incorrect implementation of laws, and the economic crisis are among the most important factors of child labour in Iran. Examination of the current situation in Iran is impossible due to a lack of transparency. The first step should be to take control of working conditions. By creating special places to work and implementing measures such as recording information about child labour status and planning to improve children’s health and education, activists can help improve children’s working status.